(untitled) (Revista científica Olimpia, 2023)
The former socialist school of sports training was victorious at the Olympic Games. The State commanded the sport and the athlete’s preparation was standardized from initiation to high performance. The objective of the review was to describe how was the sport of the former Yugoslavia. The initial development of the sport by this nation started mainly with the Sokol movement, but from 1945 after the 2nd World War conflict the Yugoslav government adopted the term physical culture used in the Soviet Union, so the sport started to be offered free for all population with the objective of form many Olympic athletes. Yugoslavia won 90 medals at the Olympic Games (28 gold, 31 silver, and 31 bronze). Yugoslavia had sports success in traditional collective sports games (basketball, handball, football, volleyball, and water polo) and some individual sports (wrestling, artistic gymnastics, and boxing). In conclusion, the Yugoslavian sport had successful with long-term work based on the Soviet model of sports preparation.